Associations between adverse childhood experiences and attempted suicide in a National sample of students in Republic of Macedonia. (7th October 2012) - Raleva, M; Jordanova-Peshevska, D; Sethi, D; Filov, I
Abstract : Background: Each year, about 4 million adolescents worldwide attempt suicide. The immediacy of the developmental stress and potential abuse and household dysfunction are experiences not easily elaborated by adolescents which at certain points may make appear the suicide to be the only solution. Objective: To assess the association between adverse childhood experiences and later suicide attempts in a sample of students in R. Macedonia. Material and methods: ACE questionnaire has been used to assess child maltreatment in a sample of 1277 students attending the secondary school or first year of university. Results: Overall suicide attempts were reported by 2.8% of respondents. Girls have attempted suicide in 4.7%, and by boys in 0.8% (p<0.05). The age when the suicide attempts were first enacted for both sexes was 14. 1.5% of girls and 0.4% of boys attempted suicide more than once. There are significant associations between attempted suicide and household dysfunction, primarily living with a family member who attempted suicide (p=0.000000), living with a family member who was mentally ill (p=0.000001) and having an alcoholic family member (p=0.000032) only for girls. There are statistically significant associations between attempted suicide and all types of abuse for both sexes. For both boys and girls there is a statistically significant association between suicide attempt and being physically abused (p=0.00000), and for girls also being emotionally abused (p=0.000000) and sexually abused (p=0.008356). Conclusions: The impact of pain and anxiety caused by emotional, sexual and physical abuse or witnessing domestic violence are experiences that can be prevented.